Taxonomy of Strategies for Coping with School Homophobic Bullying - Vicente-Cruz, Emerson [UNESP]; Saldaña, Omar; Valverde, Guillermo; de Souza, Leonardo Lemos [UNESP] (Taylor & Francis, 2025)
This study defines coping strategies in the context of homophobic bullying. A comprehensive classification of these strategies was developed based on a review of the scientific literature. Its content was reviewed by an international panel of 25 experts using a two-round Delphi method. The taxonomy has been proven to have adequate content validity and includes 15 strategies classified into three categories, namely, avoidance and self-destructive behavior, surviving the homophobic structure, and social support and promotion of egalitarian practices. According to the perceptions of the experts, the most frequently used strategies have a negative effect on the evolution of the victim’s situation, while the strategies that can have positive effects are rarely used. Victims should be encouraged to use those strategies that effectively reduce homophobic bullying, preventing further psychosocial problems.
Keywords: coping strategies; gay; Homophobic bullying; school; taxonomy; teenagers